Molecular characterization of extended-spectrum β-lactamase-producing Escherichia coli collected from patients with hematological malignancies during chemotherapy cycles - A. G. Korobova; S. A. Khrulnova; K. S. Tandilova; A. A. Novikova; G. A. Klyasova (Онкогематология, 2019)
Objective: to evaluate the genetic relatedness of extended-spectrum β-lactamase (ESBL) producing Escherichia coli isolated from the gut in patients with acute myeloid leukemia and lymphoma at admission and during chemotherapy cycles. Materials and methods. The prospective study (2013–2014) included 73 patients (median age 39 years) with acute myeloid leukemia (n = 25) and lymphoma (n = 48). The follow-up period lasted for 96 days. ESBL-producing E. coli isolated from the gut were included in this study. ESBL-production was confirmed by phenotypic tests, blaCTX-M and blaTEM genes were detected by polymerase chain reaction, and genotyping was performed by ERIC (Enterobacterial Repetitive Intergenic Consensus) polymerase chain reaction. Results. ESBL-producing E. coli were detected in 39 (53 %) of 73 patients: of them 12 (16 %) patients were colonized at admission and 27 (37 %) patients – during chemotherapy cycles. Gene blaCTX-M was detected in 67 % of E. coli, blaTEM – in 41 %, both genes – in 26 %. There was no genetically related ESBL-producing E. coli among 12 isolates detected at admission. Genetic relatedness was detected in 16 (59 %) of 27 isolates obtained during a hospital stay. Genetically related ESBL-producing E. coli were isolated from patients hospitalized in the same and different departments, these isolates were characterized by the presence of both identical and various determinants of resistance. Conclusion. Our data demonstrated the possibility of patient-to-patient transmission of ESBL-producing E. coli isolated from the gut during a hospital stay.